Exercises for mechanical neck disorders: A Cochrane review update. (August 2016) - Gross, A.R.; Paquin, J.P.; Dupont, G.; Blanchette, S.; Lalonde, P.; Cristie, T.; Graham, N.; Kay, T.M.; Burnie, S.J.; Gelley, G.; Goldsmith, C.H.; Forget, M.; et al.
Abstract: Background: Neck pain (NP) is disabling and costly. Objectives: To assess the effectiveness of exercise on pain, disability, function, patient satisfaction, quality of life (QoL) and global perceived effect (GPE) in adults with NP. Methods: We searched computerised databases up to May 2014 for randomized controlled trials (RCTs) comparing exercise to a control in adults with NP with/without cervicogenic headache (CGH) or radiculopathy. Two reviewers independently conducted selection, data abstraction and assessed risk of bias. Meta-analyses were performed to establish pooled standardised mean differences (SMDp). TheG rade ofR ecommendation, A ssessment, D evelopment andE valuation (GRADE) was used to summarise the body of evidence. Main Results: The following exercises (27 trials) were supported by 'Moderate GRADE' evidence: For chronic NP, 1) cervico-scapulothoracic and upper extremity (UE) strengthening for moderate to large pain reduction immediately post treatment (IP) and at short-term (ST) follow-up; 2) scapulothoracic and UE endurance training for a small pain reduction (IP/ST); 3) cervical, shoulder and scapulothoracic strengthening and stretching exercise for a small to large pain reduction in the long-term (LT) (SMDp −0.45 [95%CI: −0.72 to −0.18]) and function improvement; 4) cervico-scapulothoracic strengthening/stabilisation exercises for pain and function at intermediate-term (IT) (SMDp −14.90 [95%CI: −22.40 to −7.39]). 5) mindfulness exercises (Qigong) for minor improved function but not GPE (ST). For chronic CGH, cervico-scapulothoracic strengthening and endurance exercises including pressure biofeedback for small/moderate improvement of pain, function and GPE (IP/LT). Authors' conclusions: Specific strengthening exercises of the neck, scapulothoracic and shoulder for chronic NP and chronic CGH are beneficial. Future research should explore optimal dosage.